VARIABEL TRUST SEBAGAI PEMEDIASI PENGARUH ONLINE CUSTOMER REVIEW DAN KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN DI KECAMATAN AIRMADIDI KABUPATEN MINAHASA UTARA PADA E-COMMERCE SHOPEE - Loindong, Sjendry Serulo; Dotulong, Lucky.O.H.; Sumarauw, Jacky.S.B (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
This study aims to analyse the effect of Online Customer Review and product quality on consumer purchase intention, with the trust variable as a mediator, on the Shopee e-commerce platform in Airmadidi District, North Minahasa Regency. Data was collected through a survey of 100 respondents who are active Shopee users. The results showed that Online Customer Review has a significant influence on trust and consumer buying interest. Likewise, product quality has a significant effect on trust and purchase intention. Furthermore, trust is proven to have a positive and significant effect on purchase intention, as well as being a mediating variable that strengthens the influence of Online Customer Review on purchase intention. This study confirms that trust plays an important role in strengthening the relationship between online customer reviews and consumer purchase intention. This finding is expected to be a reference for e-commerce businesses in increasing customer trust through product quality and effective management of customer reviews.